2000
DOI: 10.1901/jaba.2000.33-259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High‐probability Requests on the Latency to Initiate Academic Tasks

Abstract: The purpose of this study was to evaluate the effectiveness of a high-probability request sequence on the latency to and duration of compliance to a request for completion of an independent math assignment. The participant was an elementary-school student with learning disabilities who exhibited noncompliance during math instruction. The results showed that high-probability requests were effective in reducing the latency to compliance but only minimally affected duration of engagement.DESCRIPTORS: high-probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…Ardoin, Martens, and Wolfe (1999), for example, found that a series of high-p requests reduced transition time from one instructional activity to another for a group of typical children in a general education setting. Similarly, Wehby and Hollahan (2000) found that high-p request sequences increased compliance to begin math tasks for a student with a learning disability. In addition to assessing latency to begin a math task, Wehby and Hollahan (2000) also examined student academic engagement.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Ardoin, Martens, and Wolfe (1999), for example, found that a series of high-p requests reduced transition time from one instructional activity to another for a group of typical children in a general education setting. Similarly, Wehby and Hollahan (2000) found that high-p request sequences increased compliance to begin math tasks for a student with a learning disability. In addition to assessing latency to begin a math task, Wehby and Hollahan (2000) also examined student academic engagement.…”
mentioning
confidence: 87%
“…Similarly, Wehby and Hollahan (2000) found that high-p request sequences increased compliance to begin math tasks for a student with a learning disability. In addition to assessing latency to begin a math task, Wehby and Hollahan (2000) also examined student academic engagement. These researchers found that the high-p sequence increased task engagement, but only for about 3 minutes after delivery of the sequence.…”
mentioning
confidence: 87%
“…One common characteristic of students with academic and behavior problems is failure to engage in requested tasks promptly (Allday et al 2011;Wehby and Hollahan 2000). Students who repeatedly exhibit non-compliance or excessive delays in engagement are at risk for spending less time engaged in academic tasks (Good and Beckerman 1978;Maag and Anderson 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For students who struggle academically, reducing latency to task engagement is one approach that may lead to more time devoted to academic tasks and thereby increase the potential for academic growth (Allday et al 2011;Wehby and Hollahan 2000). There is presently a growing body of work examining the use of interventions to reduce delays in classroom transitions and task compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation